2019
DOI: 10.2135/cropsci2018.10.0619
|View full text |Cite
|
Sign up to set email alerts
|

Method for Early Generation Soybean Population Selection Using F2 High‐Parent Heterosis Testing

Abstract: The germplasm pool for North American soybean [Glycine max (L.) Merr.] is narrow, and identifying novel and useful genetic diversity is time consuming and expensive. The objective of this research was to develop an early‐generation population screening method to select diversity × elite populations. The F2 high‐parent heterosis (F2 heterosis) was used as a tool to identify populations with the greatest potential for producing high‐yielding lines in subsequent generations. For Set 1 populations, six populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…These findings indicate that early selection may be efficient in soybeans, as long as it is applied with moderate intensity. Numerous studies reported favorable results with early generation testing (Friedrichs et al, 2016;Hegstad et al, 2019;Saint-Martin and Geraldi, 2002). It is noteworthy that eliminating low potential progenies is an important strategy since it enables efforts and resources to be concentrated in those with high potential for desirable traits.…”
Section: Cycle and Production From The Moderately Resistant Genotypesmentioning
confidence: 99%
“…These findings indicate that early selection may be efficient in soybeans, as long as it is applied with moderate intensity. Numerous studies reported favorable results with early generation testing (Friedrichs et al, 2016;Hegstad et al, 2019;Saint-Martin and Geraldi, 2002). It is noteworthy that eliminating low potential progenies is an important strategy since it enables efforts and resources to be concentrated in those with high potential for desirable traits.…”
Section: Cycle and Production From The Moderately Resistant Genotypesmentioning
confidence: 99%